Integrating growth, photosynthetic, and metabolomic analyses reveals how rhizobacteria affect Acanthopanax senticosus - Qi, Jiaying; Wei, Hongling; Zhang, Ye; Tang, Xiaoqing; Zhong, Weixue; Tang, Zhonghua; Liu, Ying; Li, Dewen (Frontiers in Agronomy, 2025)
The rhizosphere of soil is a highly dynamic environment involving interactions among plants, soils, and microorganisms. Microorganisms play a crucial role in facilitating plant growth and development. Acanthopanax senticosus (Rupr. & Maxim.) (A. senticosus) is an important medicinal plant in traditional Chinese medicine. However, the artificial cultivation of this species faces several challenges that have impeded the advancement of its industry. In this study, Bacillus proteolyticus (C1) and Bacillus fungorum (C2) were isolated from the rhizosphere soil of A. senticosus and identified through 16S rDNA gene sequencing. The objective was to investigate the effects of these two plant growth-promoting rhizobacteria (PGPR) on the growth, photosynthesis, and metabolism of A. senticosus. GC–MS and LC–MS were employed to screen for metabolic differences and quantify key medicinal active compounds such as eleutheroside B, chlorogenic acid, and eleutheroside E. The results indicated significant increases in plant height, leaf area, and basal diameter under C1 treatment by 81%, 10%, and 164%, respectively. A total of 29 distinct primary metabolites were detected; these metabolites enriched three common pathways where acid accumulation was significantly enhanced under C1 treatment in A. senticosus. Furthermore, 30 different phenolic compounds were identified within the phenylpropanoid biosynthesis pathway; notably, the main medicinal active substances exhibited substantial increases following C1 treatment in A. senticosus. Compared with control conditions (CK), there was a significant increase in the content of eleutheroside B and chlorogenic acid under C1 treatment (P < 0.05), with increases recorded at 346% and 183%, respectively. Additionally, yields of eleutheroside B, chlorogenic acid, and eleutheroside E in leaves from single A. senticosus plants treated with C1 showed marked improvements compared to CK conditions (P < 0.05), increasing by 466%, 259%, and 102%, respectively. These findings suggest that Bacillus proteolyticus (C1) exerts pronounced effects on promoting both growth parameters and metabolic processes within A. senticosus. This study provides a foundation for the development and application of medicinal plants based on their growth and metabolic characteristics.